The Worship Music of Dublin's Church of Ireland Parishes and Other Protestant Denominations in the Long Eighteenth Century: Sources, Repertoire and Cultural Context - Jones-Mcauley, Eleanor Mai (Trinity College Dublin. School of Creative Arts. Discipline of Music, 2022)
Studies of music in eighteenth-century Dublin have, to date, typically focussed on the musical culture of the upper-class Protestant Ascendancy, and even more specifically, on secular music. Research into sacred music has centred upon the music of the city s two cathedrals, themselves closely associated with social élites. The entirely different worship music traditions of Dublin s parish churches and non-conforming meeting houses, by contrast, have received very little attention. This thesis examines the worship music of Dublin s parish churches and meeting houses during the long eighteenth century, with three central aims: firstly, to reconstruct the various traditions of music that pertained to each Protestant community, including tune repertories and performance practice; secondly, to contextualise this worship music within both the physical environment of the church or meeting house (and of the city as a whole) and the more abstract environment of the ideologies, prejudices, debates and identities in which this music was performed and listened to; and thirdly, by so doing, to investigate the relationship between worship music and the mental world of Dublin s eighteenth-century Protestants. Through a combination of primary source analysis, an urban musicology approach to the contextualisation of music within the world of the city, and a cultural history approach which reads cultural artefacts as sources of information about the mindsets of people in the past, this thesis both adds considerably to existing knowledge about the worship music practices of eighteenth-century Protestant communities in Dublin outside of the cathedral tradition, and demonstrates that this music was shaped by, and responsive to, both the physical and mental world of those who created, participated in, talked about, and listened to it. This music is therefore a valuable source of insight into how the Protestants of eighteenth-century Dublin thought about the world around them.
APPROVED
Keywords: music; metrical psalms; sacred music; church of ireland; eighteenth-century ireland; dublin; cultural history; urban musicology; early modern ireland; parish music; nonconformist music; huguenots; hymnody; psalmody; charity children